2006
DOI: 10.1093/ajcn/84.3.523
|View full text |Cite
|
Sign up to set email alerts
|

Energy balance and the accuracy of reported energy intake in preadolescent children with cystic fibrosis

Abstract: Background: Suboptimal growth and nutritional status are common among children with cystic fibrosis (CF) and pancreatic insufficiency (PI). A better understanding of energy balance is required to improve prevention and treatment of malnutrition. Objective: Our objective was to characterize energy balance and the reporting accuracy of dietary intake in children with CF by evaluating the relations between energy intake (EI), energy expenditure (EE), fecal energy loss, nutritional status, and growth. Design: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Furthermore, there may be inaccurate reporting of nutrient intake that contributes to erroneous energy balance calculations in some chronic illnesses. In children with CF, parental report of the child's energy intake may be higher than the actual amount (22). Trabulsi et al observed overreporting of actual energy intake in a quarter of their cohort of preadolescent children with CF.…”
Section: Energy Imbalance During Chronic Illness and Its Impact On Oumentioning
confidence: 97%
“…Furthermore, there may be inaccurate reporting of nutrient intake that contributes to erroneous energy balance calculations in some chronic illnesses. In children with CF, parental report of the child's energy intake may be higher than the actual amount (22). Trabulsi et al observed overreporting of actual energy intake in a quarter of their cohort of preadolescent children with CF.…”
Section: Energy Imbalance During Chronic Illness and Its Impact On Oumentioning
confidence: 97%
“…Sample sizes in these studies ranged from 9 to 118 participants. The studies were conducted in various countries, including the USA, 4,40,42,53,55,60,61,[63][64][65][66][67]70 Sweden, 41,43,45,54,57,62 the UK, 39,44,56,58,68,69 China, 46 Australia, 47,[49][50][51]59 the Netherlands, 52 and one as a multi-center study across two countries (Belgium and Spain). 48 The age of participants varied from 1.5 to 18 years; however, one study did not provide information on the mean or range of participants' ages.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Various methods were employed to assess total EI, with the food records being the most frequently utilized dietary assessment tool. 4,39,40,42,45,47,49,53,55,59,62,63,66,[68][69][70] These studies used imageassisted food records, 40 remote food photography methods (RFPM), 42 Tool for Energy Balance in Children (TECH), 45 and weighed food records (WFR). 49,55,69 One study used computerized 24-h recall, 48 and four studies used multiple-pass 24-h recall.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment involves behavioral therapy, use of nutritional supplements, and the use of enteral diet via a nasoenteral tube in an acute phase and via gastrostomy for prolonged use. 198 - 201 …”
Section: Gastrointestinal and Nutritional Treatmentmentioning
confidence: 99%